Treatment of Anxiety in the Older Age - Novita Maulidya Jalal (Research Psychologie, Orientation et Conseil, 2024)
Anxiety in the elderly is a serious problem that can have a significant impact on the quality of life of the elderly. The aim of this research is to understand the treatment of anxiety in the elderly. The method used in carrying out this research is library research which uses 8 research journals related to anxiety and the elderly. The number of articles analyzed was 8 research articles related to anxiety in the elderly. The research results showed comprehensive treatment including psychotherapy and pharmacotherapy. Antidepressants are a treatment for end-of-life anxiety disorders, and psychotherapy, such as cognitive behavioral therapy, may be effective. The implications of this research can be used by family, friends, the community to manage anxiety, especially in the elderly.